Inhibition of Listeria monocytogenes by plantaricin NA, an antibacterial substance from Lactobacillus plantarum - Olasupo, N A (Folia microbiologica, 1998)
A Lactobacillus plantarum of vegetable origin produced a bacteriocin inhibitor to Listeria monocytogenes. The antimicrobial agent was inactivated by proteolytic enzymes, was resistant to heat (100 degrees C for 30 min) and stable over a wide pH range (pH 2-10), and displayed a bactericidal mode of action. Growth inhibition of L. monocytogenes depend on bacteriocin concentration. The antilisterial efficiency depended on the strain of L. monocytogenes used but was not influenced by the growth phase of this strain. A decrease in absorbance overtime, indicative of cell lysis, was also observed. The significance of the results is discussed in relation to the potential of the bacteriocin in controlling Listeria-associated food-borne hazards in foods.
Keywords: Food Microbiology; Temperature; potravinářská mikrobiologie; Listeria monocytogenes; Bacteriocins; nefelometrie a turbidimetrie; Lactobacillus; Nephelometry and Turbidimetry; koncentrace vodíkových iontů; teplota; bakteriociny; Hydrogen-Ion Concentration